2020
DOI: 10.1002/jcla.23467
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory abnormalities and risk factors associated with in‐hospital death in patients with severe COVID‐19

Abstract: Background In the context of the COVID‐19 outbreak of worldwide, we aim to analyze the laboratory risk factors of in‐hospital death in patients with severe COVID‐19. Methods All ≥18‐year‐old patients with confirmed severe COVID‐19 admitted to Tongji Hospital (Wuhan, China) from February 3 to February 20, 2020, were retrospectively enrolled and followed up until March 20, 2020. Epidemiological, clinical, laboratory, and treatment data were collected and explored the risk factors associated with in‐hospital deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…Further analysis revealed that CD3+, CD8+, total lymphocytes, platelets, and basophils in patients older than 50 were significantly lower than in patients younger than 50 ( P = P = .049, .018, .019, .010, and .039, respectively), while neutrophils, NLR, CRP level, and RBC RDW in patients older than 50 were significantly higher than in patients younger than 50 ( P = .0191, .015, .009, and .010, respectively) (Table 4). These results were similar to previous reports 14,28,29,38‐41 . The reduction of T‐cell subsets and the high CD4+/CD8+ T‐cell ratio are associated with disease severity; older‐aged cases tend to be more severe; thus, more lymphocytes would be consumed or severely impaired in the immune reaction.…”
Section: Discussionsupporting
confidence: 91%
“…Further analysis revealed that CD3+, CD8+, total lymphocytes, platelets, and basophils in patients older than 50 were significantly lower than in patients younger than 50 ( P = P = .049, .018, .019, .010, and .039, respectively), while neutrophils, NLR, CRP level, and RBC RDW in patients older than 50 were significantly higher than in patients younger than 50 ( P = .0191, .015, .009, and .010, respectively) (Table 4). These results were similar to previous reports 14,28,29,38‐41 . The reduction of T‐cell subsets and the high CD4+/CD8+ T‐cell ratio are associated with disease severity; older‐aged cases tend to be more severe; thus, more lymphocytes would be consumed or severely impaired in the immune reaction.…”
Section: Discussionsupporting
confidence: 91%
“…The sample size per study ranged from 27 to 1590 (total 17 879; 9686 males). Considering methodological quality in items of NOS scale, 23 studies [ 4 , 17 , 19 , 21 , 24 , 27 29 , 33 , 34 , 37 , 46 , 49 , 55 , 58 , 61 , 65 , 67 69 , 73 , 75 , 76 ] were rated as high quality (>7 stars) and 46 studies [ 18 , 20 , 22 , 23 , 25 , 26 , 30 32 , 35 , 36 , 38 45 , 47 , 48 , 50 54 , 56 , 57 , 59 , 60 , 62 64 , 66 , 70 72 , 74 , 77 84 ] were rated as moderate quality (5−7 stars). The detailed characteristics and quality of the included studies are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies [ 18 21 , 23 , 24 , 27 , 28 , 31 , 32 , 34 , 36 , 40 , 42 , 52 , 61 63 , 72 , 74 , 76 , 77 , 81 , 82 ], including 6822 patients, reported cerebrovascular disease data between non-survivors and survivors. The meta-analysis demonstrated that cerebrovascular disease was associated with death in COVID-19 patients (OR = 3.45, 95% CI: 2.46 to 4.84, P < 0.001; I 2 = 35.2%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, albumin is an independent risk factor for differentiating COVID‐19 pneumonia from influenza A pneumonia. In addition, Chen et al 21 reported that neutrophil count, hypersensitivity C‐reactive protein, creatine kinase, and blood urea nitrogen are the risk factors of COVID‐19 severe patients with poor outcomes on admission.…”
Section: Discussionmentioning
confidence: 99%